MULTIPLE CONGENITAL ANOMALIES IN A NEWBORN CALF – A CASE REPORT - P. Pothiappan; D. Selvi; K. Kantharaj; M. Thangapandiyan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A congenital anomaly is defined as an abnormality of structure or function present at birth. Multiple congenital anomalies often occur because malformation of one part of the body leads directly to malformation of another. A number of different congenital anomalies are known to occur in domestic cattle, and recently several cases of multiple congenital anomalies have been reported in cattle (Lapointe et al., 2000; Agerholm et al., 2001; Duncan et al., 2001). The present paper reports congenital anomalies viz imperforate ani, bifid vulva and ventral hernia in a newborn calf.